2006
DOI: 10.1007/s00442-006-0493-1
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and myocarditis in voles and lemmings at cyclic peak densities—induced by Ljungan virus?

Abstract: Although it is well-documented from theoretical studies that pathogens have the capacity to generate cycles, the occurrence and role of pathogens and disease have been poorly empirically studied in cyclic voles and lemmings. In screening for the occurrence of disease in cyclic vole and lemming populations, we found that a high proportion of live-trapped Clethrionomys glareolus, C. rufocanus, Microtus agrestis and Lemmus lemmus at high collective peak density, shortly before the decline, suffered from diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 48 publications
1
32
1
2
Order By: Relevance
“…Our most recent case-control study shows no difference in positivity for human parechovirus infections in stool samples (Tapia et al, 2010). Ljungan virus has earlier been shown to cause diabetes-like condition in rodents (Niklasson et al, 2006), but was not identified in samples from children in our studies (Tapia et al, 2008, Tapia et al, 2010. HPeV1 has been reported to show no association with T1D (Tauriainen et al, 2007), but there is no data on the other types of HPeVs.…”
Section: Picornaviruscontrasting
confidence: 64%
“…Our most recent case-control study shows no difference in positivity for human parechovirus infections in stool samples (Tapia et al, 2010). Ljungan virus has earlier been shown to cause diabetes-like condition in rodents (Niklasson et al, 2006), but was not identified in samples from children in our studies (Tapia et al, 2008, Tapia et al, 2010. HPeV1 has been reported to show no association with T1D (Tauriainen et al, 2007), but there is no data on the other types of HPeVs.…”
Section: Picornaviruscontrasting
confidence: 64%
“…LV has been associated with several human diseases [26,[28][29][30][31], and causes symptoms in laboratory mice [28], but LV has yet to be isolated from humans or proven a causative agent of disease. High seroprevalence (36%, 38%) to LV has recently been detected in humans in Finland [15], indicating a fairly high exposure to LV and/or to an antigenically-related virus in early childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Ljungan virus (LV) is a picornavirus recently isolated from different vole species (Clethrionomys glareolus, C. gapperi, Microtus montanus, M. pennsylvanicus) in Sweden and on the American continent (5,16,18,19,22,26,43). LV cause diabetes, myocarditis and other diseases in rodents, and LV has also been suggested to be involved in human diseases (25)(26)(27)(28)(29)(30)34). LV was recently associated with intrauterine fetal deaths in humans (31).…”
mentioning
confidence: 99%